How do board ties affect the adoption of new practices? The effects of managerial interest and hierarchical power. (4th September 2019) - Yoshikawa, Toru; Shim, Jung Wook; Kim, Chang Hyun; Tuschke, Anja
Abstract: Research Question/Issues: Most extant literature implicitly equates obtaining information through board interlocks to acting on the information. We investigate triggers that help to translate the information into action. In addition to exposure to the information by board interlocks, we suggest that the self‐interest of the individuals who create these ties and hierarchical power of interlinked firms determines the likelihood of taking actions of adopting new practices. Research Findings/Insights: Using the action of adopting two distinctive governance practices, stock option pays or board reform, we find that sent ties and received ties affect the adoption decisions differently. Whereas sent ties reflect managerial interests, received ties derive power from a hierarchical relationship between the focal firm and the interlinked firm. Such differential nature of sent and received ties drives a differential result in terms of adopting two distinctive governance practices. We also find support for different moderating effects of firm performance on the impact of sent and received ties. Theoretical/Academic Implications: In this study, we incorporated the self‐interest of executives with sent ties to prior adopters and the power of directors who establish ties with prior adopters that are hierarchically positioned. By doing so, this study paints a more fine‐grained picture regarding underlying mechanisms by which information gained through ties is translated into action. This provides important insights for both agency theory and resource‐dependency theory. Practitioner/Policy Implications: Hierarchical board ties are not a unique phenomenon in Japan. We often find such ties in business groups in China, India, Korea, and some European countries. Establishing board interlocks among subsidiaries in a business group is an important governance resolution for controlling the whole business group. Hence, our findings that the ties carry not only information but also agent's interest and hierarchical power should be taken into account when a business group designs board interlocks.